Pengaruh Citra Destinasi dan Promosi Terhadap Kepuasan Wisatawan di Puncak Sempur Kabupaten Karawang - Katon Van Daffa; Ina Ratnasari (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to obtain a systematic description of the destination image and promotion variables as independent variables and tourist satisfaction as the dependent variable in Puncak Sempur, Karawang Regency. The approach in this study is a descriptive approach and a verification approach. According to Sugiyono (2017:147) Descriptive analysis is statistics used to analyze data by describing or describing the data that has been collected as it is without intending to make conclusions that apply to the public or generalizations. The results of the study show that: 1) There is a correlation between Destination Image and Promotion with a correlation coefficient value of 0.735 and has a strong relationship level because the value is positive. 2) There is a partial effect of Destination Image and Promotion on Tourist Satisfaction. 3) There is a simultaneous influence of Destination Image and Promotion on Tourist Satisfaction of 79.4%, while the remaining 20.6% is the influence of other factors not examined in the study. This can indicate that Destination Image and Promotion together have an influence on Tourist Satisfaction on Puncak Sempur tourism